2011
DOI: 10.1111/j.1442-200x.2010.03309.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal level of 25‐(OH)D in children in Nanjing (32°N Lat) during winter

Abstract: The optimal 25-(OH)D level may be 50-60 nmol/L for bone health in Nanjing children. The vitamin D nutritional status of Nanjing children is relatively good in winter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…Similar to the study in Nanjing, vitamin D deficiency occurred in 1.3% of healthy children and in 16.7% of sick children aged one to 10 years [14]. This phenomenon may be ascribed to vitamin D reinforcing immunomodulation [32] through its complicated effects on macrophages and lymphocytes [33], as 25(OH)D is a negative acute-phase reactant of disease.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Similar to the study in Nanjing, vitamin D deficiency occurred in 1.3% of healthy children and in 16.7% of sick children aged one to 10 years [14]. This phenomenon may be ascribed to vitamin D reinforcing immunomodulation [32] through its complicated effects on macrophages and lymphocytes [33], as 25(OH)D is a negative acute-phase reactant of disease.…”
Section: Discussionmentioning
confidence: 65%
“…Another study in Shanghai (31° N latitude) showed that almost one-third newborns had 25-hydroxyvitamin D (25(OH)D) less than 20 ng/mL [13]. Serum 25(OH)D < 20 ng/mL and 25(OH)D < 10 ng/mL occurred in 10.5% and in 1.3% of healthy children under 10 years of age in Nanjing (32° N) from December to March [14]. A study in southeast China found that vitamin D deficiency (<20 ng/mL) and insufficiency (20–29 ng/mL) were prevalent among infants, preschool children, school children and adolescents in Wenzhou [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Vieth et al suggested that the maximal inhibition of parathyroid hormone (PTH) by circulating 25(OH)D occurred at the concentrations of 25(OH)D > 80 nmol/L [17]. Some studies including our previous studies supported that when the concentrations > 75 nmol/L, the PTH levels plateaued [18]. But in late 2010, the IOM reported another statement that the concentrations of 25(OH)D > 50 nmol/L was sufficient for bone health.…”
Section: Introductionmentioning
confidence: 87%
“…Vitamin D Vitamin D deficiency rates were reported in different parts of China (52)(53)(54)(55)(56) (Table 3). The prevalence of severe vitamin D deficiency was found to be 45?2 % in winter and 6?7 % in summer among adolescents in Beijing (55) .…”
Section: Vitamin Bmentioning
confidence: 99%